Blockade of Bradykinin receptors worsens the dystrophic phenotype of mdx mice: differential effects for B1 and B2 receptors - Jose Acuna, Maria; Salas, Daniela; Cordova-Casanova, Adriana; Cruz-Soca, Meilyn; Cespedes, Carlos; Vio, Carlos P.; Brandan, Enrique (My University, 2018)
The Kallikrein Kinin System (KKS) is a vasoactive peptide system with known functions in the maintenance of tissue homeostasis, renal function and blood pressure. The main effector peptide of KKS is Bradykinin (BK). This ligand has two receptors: a constitutive B2 receptor (B2R), which has been suggested to have anti-fibrotic effects in renal and cardiac models of fibrosis; and the inducible B1 receptor (B1R), whose expression is induced by damage and inflammation. Inflammation and fibrosis are hallmarks of Duchenne muscular dystrophy (DMD), therefore we hypothesized that the KKS may play a role in this disease. To evaluate this hypothesis we used the mdx mouse a model for DMD. We blocked the endogenous activity of the KKS by treating mdx mice with B2R antagonist (HOE-140) or B1R antagonist (DesArgLeu(8)BK (DALBK)) for four weeks. Both antagonists increased damage, fibrosis, TGF-beta and Smad-dependent signaling, CTGF/CCN-2 levels as well as the number of CD68 positive inflammatory cells. B2R blockade also reduced isolated muscle contraction force. These results indicate that the endogenous KKS has a protective role in the dystrophic muscle. The KKS may be a new target for future therapies to reduce inflammation and fibrosis in dystrophic muscle.
Keywords: kallikrein kinin system; bradykinin receptors b1 and b2; muscular dystrophy; fibrosis; inflammation